A Modified Zinc Acetate Gel, a Potential Nonantiretroviral Microbicide, Is Safe and Effective against Simian-Human Immunodeficiency Virus and Herpes Simplex Virus 2 Infection In Vivo - Kenney, Jessica (2013)
We previously showed that a prototype gel comprising zinc acetate (ZA) in carrageenan (CG) protected mice against vaginal and rectal herpes simplex virus 2 (HSV-2) challenge as well as macaques against vaginal simian-human immunodeficiency virus reverse transcriptase (SHIV-RT) challenge. In this work, we modified buffers and cosolvents to obtain a stable, nearly iso-osmolal formulation and evaluated its safety and efficacy against SHIV-RT and HSV-2. In vitro toxicity to lactobacilli and Candida albicans was determined. Macaques were given daily doses of ZA and CG (ZA/CG) or CG alone vaginally for 14 days and challenged with SHIV-RT 24 h later. Mice were challenged vaginally or rectally with HSV-2 immediately after a single gel treatment to measure efficacy or vaginally 12 h after daily gel treatment for 7 days to evaluate the gel's impact on susceptibility to HSV-2 infection. The modified ZA/CG neither affected the viability of lactobacilli or C. albicans nor enhanced vaginal HSV-2 infection after daily ZA/CG treatment. Vaginal SHIV-RT infection of macaques was reduced by 66% (P = 0.006) when macaques were challenged 24 h after the last dose of gel. We observed 60% to 80% uninfected mice after vaginal (P < 0.0001) and rectal (P = 0.008) high-dose HSV-2 challenge. The modified ZA/CG gel is safe and effective in animal models and represents a potential candidate to limit the transmission of HIV and HSV-2.